Heavy metals in the moss gametophyte Bryum argenteum Hedw. and in the soil inside the plant in Nikolaev (Ukraine) (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
In the surroundings of the four factories in the city of Mykolaiv (Ukraine) research was carried out and the content of heavy metals – Cu. Zn, Cd, Pb in soils and gametophyte of moss Bryum argenteum was analysed. Also the coefficients of accumulation of heavy metals in soils were analyzed at surrounding territories of factories of Mykolaiv city (Mykolayiv Alumina Plant, Research and Production Complex of Gas Turbine "Zorya"- "Mashproject", JSC "Damen Shipyards Ocean" and Shipyard named after 61- Communards) 1-1,5 times higher than coefficients of accumulation gametophyte of investigated moss. The least contaminated in comparison with conditionally pure area is the territory and the surroundings of the factory of 61-Communards. These data confirm that this type of moss refers to indicator plants.
Keywords: heavy metals, bryophytes, soils, Вryum аrgenteum, Ukraine.